Metode pembebanan langsung dan harga pokok penjualan (Studi kasus GB Kitchen Manado) - Tampongangoi, Yunlika; Pontoh , Winston; Maradesa, Djeini (Manajemen Bisnis dan Keuangan Korporat, 2024)
The direct assignment method is a method of determining the cost of production that only takes into account production costs that are directly related to the production process. This research aims to determine the application of the direct charging method and cost of goods sold at GB Kitchen Manado. The research method used is descriptive qualitative. The research results show that the calculation of the cost of goods manufactured by GB Kitchen is higher compared to the direct charging method, which results in the calculation of the cost of goods sold. For the chocolate cheese pastry roll product, the direct charge method produces a total cost of production of IDR 18,120,576, while the cost of goods sold is IDR 17,848,776. For chocolate snail cake products, the total cost of production is IDR 7,114,432, and the cost of goods sold is IDR 7,009,530.